2016
DOI: 10.3389/fphar.2016.00170
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties of Menthol and Menthone in Schistosoma mansoni Infection

Abstract: Schistosomiasis is a parasitic disease caused by several species of trematode worms and it is believed that more than 261 million people are affected worldwide. New drug development has become essential because there is a risk of the parasite becoming resistant to Praziquantel, the only drug available for this infection. This study evaluated parasitological, immunological and histological parameters in mice infected with Schistosoma mansoni and treated with an herbal commercial medicine. This drug consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…IL-10 undoubtedly plays a key role in controlling infection (Coutinho et al, 2010). The same results were reported in several studies on different experimental animals (El-Sisi et al, 2011;Zaia et al, 2016). In the current study, infected mice treated with PZQ showed an increase in the level of IL-10.…”
Section: Discussionsupporting
confidence: 90%
“…IL-10 undoubtedly plays a key role in controlling infection (Coutinho et al, 2010). The same results were reported in several studies on different experimental animals (El-Sisi et al, 2011;Zaia et al, 2016). In the current study, infected mice treated with PZQ showed an increase in the level of IL-10.…”
Section: Discussionsupporting
confidence: 90%
“…It shares important biological activities of other mint herbs members like antioxidant, anti-inflammatory and anticancer. These activities are attributed to the presence of total phenol terpenoids and flavonoids content [3][4][5][6][7]. Niture et al studied the alterations in O-6-methyl guanine DNA methyl transferase (MGMT) activities of the water soluble and alcohol soluble constituents of closely related specie of spear mint (M. viridis) in human peripheral blood lymphocyte and cancer cell Lins [8].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the fresh leaves are used as a raw vegetable or flavoring herb, whereas the dried leaves are traditionally used for herbal tea or medicine. Mint herbs have been reported to possess several biological effects, including antioxidant, anti-inflammatory, anticancer, and antimicrobial activities ( Tang et al, 2016 ; Zaia et al, 2016 ; Wang et al, 2018 ). These biological activities of spearmint are significantly correlated with their total phenol flavonoid content ( Manosroi et al, 2006 ; Santos et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%